Božja Napaka - Mataranz, Eva; Savchenko, Anna (Slovenia : Luksuz Produkcija, 2014)
'God's Mistake' is a documentary about Salomé, a young woman from former-Yugoslavia, who in everyone else's eyes was born as a little boy. Eva Mataranz and Anna Savchenko explore Salomé's experiences a transgender woman; the threats, military service, school and religion couldn't shake Salomé's innate commitment to transition.
Verzio Film Festival Submission
Keywords: Documentary films